Identifikasi Infeksi Soil transmitted helminth pada Feses Orangutan Kalimantan dengan Metode Natif di Kebun Binatang Medan - Limbong, Lasmega R; Fauziah, Ida; Sartini, Sartini; Rahmiati, Rahmiati (Universitas Medan Area, 2023)
Orangutans are the only great apes that inhabit Sumatra and Borneo, but the Bornean orangutan (Pongo pygmaeus) is critically endangered due to health-related issues. Orangutans in zoos or captivity face a higher risk of parasitic infections compared to those in their natural habitats. This is attributed to the unsuitable environmental conditions, such as confined enclosures that restrict their movements and daily activities. Conservation efforts are crucial to prevent orangutan extinction, including ex-situ conservation at Medan Zoo. However, ex-situ conservation also poses the risk of infection by soil-transmitted helminths, nematodes that require soil to reach their infective stage. This research aims to identify the species of soil-transmitted helminths (STH) in Bornean orangutan fecal samples and assess the level of infection. The research method involves descriptive analysis and fecal examination using the native method with six fecal samples from two orangutan individuals. The results revealed the presence of three types of soil-transmitted helminth eggs in both orangutans: Ascaris lumbricoides, Trichuris trichiura, and Necator americanus. The infection level falls into the moderate category (500-5000 eggs).